Governance and institutional risks and challenges in Nepal Shrestha, Rachana. - Shrestha, Rachana (Asian Development Bank, 2019)
With the adoption of its new constitution on 20 September 2015, Nepal became a federal democratic republic. Since then, the countrys transition from a unitary system of government to the new federal system has been ongoing and remains a challenging process. The report examines the evolving institutional arrangements, challenges, and governance risks for the sectors in which ADB operates. It also identifies potential reform measures that ADB could support to help address these governance risks. The report aims to contribute to the preparation of ADBs 2020-2024 country partnership strategy for Nepal.